A Facile Surface Modification Strategy for Antibody Immobilization on 3D-Printed Surfaces - Brandi Binkley; Peng Li (Biosensors)
3D-printed microdevices have become increasingly important to the advancement of point-of-care (POC) immunoassays. Despite its great potential, using 3D-printed surfaces on the solid support for immunorecognition has been limited due to the non-ideal adsorption properties for many photocurable resins. In this work, we report a simple surface modification protocol that works for diverse commercial photocurable resins, improving ELISAs performed directly on 3D-printed devices. This surface modification strategy involves surface activation via air plasma followed by the one-step incubation of GLYMO-labeled streptavidin. We successfully immobilized biotinylated anti-activin A antibodies on the 3D-printed surfaces and performed the complete ELISA protocol on the 3D-printed surfaces. We demonstrated that this protocol achieved an improved performance over passive adsorption for ELISAs. The present method is also compatible with diverse commercial resins and works with both microwells and microchannels. Finally, this method demonstrated a comparable limit of detection to the ELISA performed using commercial microwells. We believe the simplicity and broad compatibility of the present surface modification strategy will facilitate the development of 3D-printed POC ELISA devices.